The Significance of Interpersonal Communication as A Mechanism for Social Relationships in the Career Development of Employees At “Seia Sekata Roastery & Espresso Bar” In Cirebon City - Kayla Auralianie Karin; Farida Nurfalah (Indonesian Journal Publisher, 2026)
The informal sector, which is based on the creative economy, provides flexible workplaces with work relations that vary to that of the formal organization. Interpersonal communication in this case is an essential aspect in the organization of work and social relations. This study aims at analyzing the meaning, processes and the purpose of interpersonal communication networks among the employees in Seia Sekata Roastery and Espresso Bar in Cirebon in enabling career development. The study strategy is qualitative in the form of a phenomenological one using in-depth interviews with five informants (first in the list of which are roastery staff, roastery assistant, barista, and social media manager) and one supporting informant (in the position of the HR department). Relevant books, articles, and journals were used to extract secondary data to reinforce the analysis of research findings. The results indicate that the employees develop their attitudes towards interpersonal communication as a significant factor in their career sustainability on the basis of recurrent communication experiences. The values of openness, empathy, support, positive attitude and equality as described by DeVito are a platform upon which relationships at work are strengthened and trust, mutual norms and supportive relationships develop as a source of social capital. This social capital is utilized in the promotion of career development and strengthening of employees work role in such a way that interpersonal communication is not only employed as a channel of information sharing but also employed as a foundation on which sustainable social relationship is developed to help individual career development.